2017
DOI: 10.3808/jei.201700370
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Ecological Factors on Nonpoint Source Pollution in the Upper Reach of the Yangtze River

Abstract: Nowadays, nonpoint source pollution has been a dominant cause of water quality deterioration and eutrophication. For large basins, long-term effects of ecological factors on nonpoint source pollution are significant and have gained worldwide attention. Yangtze River is the largest river in China, and water environment protection of its upper reach is crucial to maintain the whole river health and the Three Gorges Project successful operation. The objective of this study is to reveal the effects of ecological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…It was further shown that the loss of sediment and adsorbed pollutants was related to soil erosion and pollutant characteristics. These results are consistent with previous studies [2,22], indicating that anthropogenic factors were main sources of dissolved pollutants, and ecological factors were main sources of sediment and adsorbed pollutants.…”
Section: Effects Of Various Anthropogenic Factors On Nps Pollutionsupporting
confidence: 93%
See 4 more Smart Citations
“…It was further shown that the loss of sediment and adsorbed pollutants was related to soil erosion and pollutant characteristics. These results are consistent with previous studies [2,22], indicating that anthropogenic factors were main sources of dissolved pollutants, and ecological factors were main sources of sediment and adsorbed pollutants.…”
Section: Effects Of Various Anthropogenic Factors On Nps Pollutionsupporting
confidence: 93%
“…It was further shown that the loss of sediment and adsorbed pollutants was related to soil erosion and pollutant characteristics. These results are consistent with previous studies [2,22], indicating that In terms of DN, the annual loads caused by rural life, livestock breeding, land use and atmospheric deposition all showed an upward trend from 1960 to 2000, and declined by 2003. The contribution rate of rural life to the total pollution load decreased, and the contribution rate of livestock breeding did not change significantly.…”
Section: Effects Of Various Anthropogenic Factors On Nps Pollutionsupporting
confidence: 93%
See 3 more Smart Citations